Proceedings 2014 Workshop on Usable Security 2014
DOI: 10.14722/usec.2014.23045
|View full text |Cite
|
Sign up to set email alerts
|

Should I Protect You? Understanding Developers' Behavior to Privacy-Preserving APIs

Abstract: There have been many proposals and developments to improve smartphone users' location privacy with respect to mobile applications. These include user-centric application permission models and disclosures. However, little attention has been paid to how application developers could build privacypreserving apps. In this paper, we present a laboratory study (N=25) to understand developers' behavior to enhanced APIs, which are a privacy-preserving modification of the existing Android Location API. In contrast to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…In our sample, 34 papers include quotes from participants. For example, Jain and Lindqvist incorporate relevant quotes in the text which fosters the results validity and also work as examples of how authors interpret the interviews [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, 34 papers include quotes from participants. For example, Jain and Lindqvist incorporate relevant quotes in the text which fosters the results validity and also work as examples of how authors interpret the interviews [66].…”
Section: Discussionmentioning
confidence: 99%
“…The features provided by readily available APIs can also impact security and privacy choices of developers. In a case of geo-location libraries, developers who have access to a library with privacy-preserving options are more willing to use coarse location information over those with only access to the standard library [66].…”
Section: F Application Programming Interfaces (Apis)mentioning
confidence: 99%
“…Balebako et al performed interviews and online surveys to investigate how app developers make decisions about privacy and security, identifying several hurdles and suggesting improvements that would help user-privacy [3,4]. Jain et al suggested design changes to the Android Location API based on the results of a developer lab study [32]. Fahl et al and Oltrogge et al conducted developer surveys and interviews, revealing deficits in the handling of TLS/SSL and suggesting several improvements [20,21,41].…”
Section: Related Workmentioning
confidence: 99%
“…Obvious further work would be to understand if the shortened Request permission, in addition to being cost-effective, is effective in informing app consumers and helps them to make appropriate decisions. In our previous work, we have also explored alternative approaches to mobile app security & privacy, including explicitly showing users when their location is requested [11], showing network accesses of apps with Securacy [10], automated app analysis [2], crowdsourced privacy mental models [17] and privacy-preserving API design [13].…”
Section: Discussionmentioning
confidence: 99%